Edible coating with coconut water to preserve probiotic strains and sensory characteristics of minimally processed carrots - Shigematsu, E.; Dorta, C.; Santos, D. N.; Ferreira, K. A.; Goes-Favoni, S. P.; Oshiiwa, M.; Mauro, M. A. [UNESP] (Univ Putra Malaysia Press, 2019)
The present work evaluated the protective effect of coconut water on the bacterium Lactobacillus acidophilus LA3 added to an edible sodium alginate-based coating, as well as its effect on the preservation of the sensory quality of minimally processed carrots. Treatments were employed based on alginate and the probiotic, with and without addition of coconut water to the coating applied on the carrots. The coconut water improved the bacterium's cell viability for seven days, rendering this coating three log cycles superior to the coating without coconut water. After 21 days, carrots with this coating had counts above log 6 CFU/g, which is a recommended level for health benefits, while the other treatment did not present viable cells within the detection limit of the method (10(-4) dilution). The panellists showed greater acceptance and purchase intention for the coating containing coconut water throughout the storage period of the samples than for the control carrots. (C) All Rights Reserved
Keywords: Edible coating; Sodium alginate; Cocos nucifera L.; Lactic bacteria